On the nature of wind-forced upwelling in Barrow Canyon. (April 2019) - Pisareva, Maria N.; Pickart, Robert S.; Lin, Peigen; Fratantoni, Paula S.; Weingartner, Thomas J.
Abstract: Using time series from a mooring deployed from 2002 to 2004 near the head of Barrow Canyon, together with atmospheric and sea-ice data, we investigate the seasonal signals in the canyon as well as aspects of upwelling and the wind-forcing that drives it. On average, the flow was down-canyon during each month of the year except February, when the up-canyon winds were strongest. Most of the deep flow through the head of the canyon consisted of cold and dense Pacific-origin winter water, although Pacific-origin summer waters were present in early autumn. Over the two-year study period there were 54 upwelling events: 33 advected denser water to the head of the canyon, while 21 upwelled lighter water due to the homogeneous temperature/salinity conditions during the cold season. The upwelling occurs when the Beaufort High is strong and the Aleutian Low is deep, consistent with findings from previous studies. Most events resulted in the reintroduction of Pacific Winter Water onto the Chukchi Shelf, rather than advection of Atlantic Water. Overall there were more than twice as many upwelling events during the cold season as the warm season due to the seasonal strengthening of the winds. An analysis of temporally integrated measures revealed a statistically significant relationship between the atmospheric forcing and upwelling response, such that stronger storms tend to result in stronger upwelling. Finally, it is demonstrated that upwelling typically corresponds to the occurrence of the Northeast Chukchi Polynya.